Characteristics of groundwater microbial communities and the correlation with the environmental factors in a decommissioned acid in-situ uranium mine - Zhu, Fangfang; Zhao, Bei; Min, Wenwen; Li, Jiang (Frontiers in Microbiology, 2023)
Microorganisms play an important role in the bioremediation process for the decommissioned acid in-situ leaching uranium mine. It is crucial to understand the original microbial community characteristics before the in-situ bioremediation. However, there are limited studies on the groundwater microbial characteristics in the decommissioned acid in-situ uranium mine. To this end, we collected groundwater samples, including the groundwater that originally residual in the borehole (RW) and the aquifer water (AW), from a decommissioned acid in-situ uranium mine in the southern margin of Ili Basin in Xinjiang, China. The occurrence characteristics of the groundwater microbial communities and their correlation with environmental factors were systematically studied based on the high throughput 16S rRNA gene sequencing data and geochemical data. Results found that the AW samples had higher alpha- and beta- diversity than the RW samples. The relative abundance of Sporosarcina, Sulfobacillus, Pedobacter and Pseudomonas were significantly different in the AW and RW samples, which had significant correlation with pH, metals, and sulfate, etc. A series of reducing microorganisms were discovered, such as sulfate reduction (e.g. Desulfosporosinus) and metal reduction (e.g. Arthrobacter, Bacillus, Clostridium, Pseudomonas, Rhodanobacter), which have the potential to attenuate sulfate and uranium in groundwater. In addition, we found that pH and redox potential (Eh) were the dominant environmental factors affecting the microbial composition. This study extends our knowledge of microbial community structure changes in the decommissioned acid in-situ uranium mine and has positive implications for assessing the potential of natural attenuation and bioremediation strategies.